THE MECHANICAL PROPERTIES OF SOLIDIFIED POLYETHYLENE GLYCOL 600, AN ANALOG FOR LAVA CRUST - Soule S.A.; Cashman K.V. (My University, 2004)
The strength of lava crust and the role of that crust in determining lava flow dynamics and morphology are of fundamental importance in modeling lava flow behavior. Great improvements to flow models have been made by combining theoretical analysis with the results from analog experiments using polyethylene glycol (PEG 600) wax, which solidifies just below room temperature and can be used to simulate solidifying flows. However, a paucity of experimental data on the mechanical properties of solid PEG 600 has limited the quantitative interpretation of the role of crust in these experiments. We have, therefore, conducted experiments to measure the mechanical properties (tensile strength, shear strength, and Young's modulus) of solidified PEG 600 at temperatures and strain rates similar to those employed in analog experiments. The mechanical properties of PEG 600 can be modeled by a power law function of temperature, with the tensile strength exhibiting an additional dependence on strain rate. At intermediate temperatures, marked changes in the temperature dependence of the Young's modulus and in the character of failure surfaces indicate a transition from brittle to ductile behavior. We find that the strength of solid PEG 600 at experimental temperatures and strain rates exceeds that inferred for the crust on active laboratory flows by four orders of magnitude. This discrepancy is best explained by the presence of a thin visco-elastic layer separating the solid surface from the fluid interior of PEG 600 flows, a model that has been suggested to explain the behavior of some basaltic lava flows.
Keywords: LAVA FLOW; CRUST; PEG 600; RHEOLOGY; TENSILE STRENGTH